Guiling prescription attenuates hyperuricemia via multi-target regulation of uric acid metabolism, renal protection, and inflammation: insights from metabolomics and network pharmacology - Wang, YuKun; Ding, RenJie; Guo, Yaxuan; Zhou, TianHui; Zhao, Huichun; Liu, HuiWu; Qin, XueMei; Gao, XiaoXia (Frontiers in Nutrition, 2026)
BackgroundThis study aims to evaluate the efficacy of Guiling Prescription (GP)—a medicinal food homologous formula—in hyperuricemic rats, its effects on uric acid excretion and renal function, and to clarify the metabolic mechanisms involved in GP's alleviation of hyperuricemia.MethodsSprague-Dawley (SD) rats of hyperuricemia was established using potassium oxonate (200 mg/kg, PO) and adenine (100 mg/kg) to assess the therapeutic effects of Guiling Prescription (GP). We measured body weight, serum levels of uric acid and creatinine, as well as xanthine oxidase (XOD) and adenosine deaminase (ADA) activity, alongside histopathological parameters. Serum concentrations of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and alanine aminotransferase (ALT), and aspartate aminotransferase (AST) were determined using ELISA kits. The expression of renal uric acid transporters was evaluated through Western blotting. Network pharmacology was utilized to predict the key drug-disease targets, and a non-targeted metabolomic assay was applied to identify the key metabolites and metabolic pathways, and validated these targets through molecular docking and western blot analyses.ResultsGP showed an improvement effect on hyperuricemia model rats, with decreased levels of serum uric acid (UA), serum urea nitrogen, and creatinine, and serum ALT, AST. Furthermore, H&E staining results showed to improve renal injury in the hyperuricemic rat, and serum interleukin-6 and tumor necrosis factor-αwere improve the body's inflammatory response after administration of GP. In addition, GP could regulate multiple serum metabolic pathways such as arachidonic acid metabolism, pyrimidine metabolism, purine metabolism, citric acid cycle. On one side, GP decreased the synthesis of uric acid by inhibiting hepatic xanthine oxidase activities and adenosine deaminase activity. On the other side, GP increased the excretion of uric acid with the upregulation of UA excretion genes ABCG2, OAT1, and OAT3 and downregulation of UA resorption genes URAT1 and GLUT9.ConclusionGP orchestrates uric acid metabolism through multi-target and multi-pathway regulation, highlighting its potential not only as a novel therapeutic strategy but also as a promising dietary supplement for the management of hyperuricemia.